Improving Energy Consumption in Networks on Chip using Optimized Algorithms - Taassori, Mehdi (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2016)
Network on Chip (NoC) has been suggested as an appropriate and scalable solution for system on chip (SoC) architectures having high communication demands. Power dissipation has become a key factor in the NoCs because of their shrinking sizes. In the first part of the thesis, we propose a new encoding approach aimed at power reduction by decreasing the number of switching activities on the buses. This approach assigns the symbols to data word in such a way that the more frequent words are sent by less power consumption. This algorithm dedicates the symbols with less ones to high probable data and uses transition signaling to transmit data. The proposed method, unlike the existing low power encoding, does not rely on spatial redundancy and keeps the width of the bus constant. Due to the limitation of the resources in NoC, suitable load distribution over limited resources which is known as mapping optimization problem is a challenging issue. The second part presents an OPtimization technique for Application specifIC NoCs (OPAIC), which aims not only to decrease the energy consumption but also to improve the performance and area of NoCs. Application specific NoCs are preferable since they can be customized to optimize all requirements of the specific applications. OPAIC is composed of two stages to find the optimum NoC; in the first stage, it uses a linearized form of a Quadratic Assignment Problem (QAP) to map tasks on cores to minimize the energy dissipation. In the second stage, due to the colossal effect of router reduction on power consumption of NoC, a Mixed Integer Linear Problem (MILP) is proposed to find the optimum number of the routers for the layout earned in previous stage. It is also worth mentioning that even though in most of the traditional low power encoding algorithms and optimization techniques the effect of coupling capacitors is ignored, the results show that these capacitors have an increasing contribution in power consumption in the NoCs as the VLSI technology advances and the size of the transistor shrinks. In this dissertation, all evaluation results consider the effect of both self and coupling capacitances in the link power dissipation. Keywords: Network on Chip, low power encoding, switching activity, power consumption, energy dissipation, latency, application specific, optimization, mapping

Öz: Mikro Çip üzerindeki Ağ (MÇüA), Mikro Çip üzerindeki Sistem (MÇüS) mimarileri için yüksek iletişim taleplerine sahip uygun ve ölçeklenebilir bir çözüm olarak önerilmiştir. Küçülen boyutları yüzünden MÇüA’lardaki güç tüketimi oldukça önemli bir faktör haline gelmiştir. Bu tez çalışmasının ilk bölümünde veri yolları üzerindeki anahtarlama sayılarını azaltarak güc tüketiminin düşürülmesini hedefleyen yeni bir şifreleme yaklaşımı önerilmiştir. Bu yaklaşım, daha sık kelimelerin daha düşük güç tüketilerek gönderileceği şekilde sembolleri veri kelimelerine atamaktadır. Bu algoritma daha düşük bir sayılarına sahip sembolleri yüksek olasılıklı verilere tahsis edip veri gönderimi için geçiş sinyalizasyonunu kullanmaktadır. Önerilen yöntem, mevcut olan düşük güçlü şifreleme yönteminin tersine, mekânsal fazlalığa dayanmamakta ve veri yolu genişliğini korumaktadır. MÇüA kaynaklarındaki sınırlılık dolaysıyla haritalama optimizasyon problemi olarak bilinen sınırlı kaynaklar üzerindeki uygun yük dağılımı tartışma konusu olmuştur. İkinci bölüm, yalnızca güç tüketiminin düşürülmesini hedef almayıp aynı zamanda MÇüA’ların performansı ve alanını da geliştirmeyi amaçlayan Uygulamaya Özel MÇüA’lar için Optimizasyon Tekniği’ni (UÖMOP) sunmaktadır. Belirli uygulamaların tüm gereksinimlerini iyileştirmek üzere özelleştirilebilme özellikleri Uygulamaya özel MÇüA’ları tercih edilebilir kılmıştır. UÖMOP, ideal MÇüA’yı bulmak için iki aşamadan oluşmuştur. Birinci aşamada, enerji tüketiminin en aza indirgenmesi amacıyla çekirdekler üzerinde görevleri planlamak üzere Kareli Atama Problemi’nin (KAP) lineerleştirilmiş bir şekli kullanılmaktadır. İkinci aşamada ise yönlendirici indirgemesinin MÇüA’nin güç tüketimi üzerindeki muazzam etkisi nedeniyle bir önceki aşamada elde edilen düzen için ideal yönlendirici sayısının bulunması amacıyla bir Karışık Tamsayı Lineer Problemi (KTLP) önerilmiştir. Geleneksel düşük güçlü şifreleme algoritmaları ve optimizasyon tekniklerinin çoğunda bağlantı kapasitörlerinin etkisi dikkate alınmasa bile sonuçların Çok Büyük Boyutlu Entegrasyon (ÇBBE) Teknolojisinin ilerlemesi ile birlikte bu kapasitörlerin MÇüA’lardaki güç tüketimi konusunda artan bir katkıya sahip olduklarını gösterdiği bahsetmeye değer bulunmaktadır. Anahtar Kelimeler: Mikro Çip üzerindeki Ağ, düşük güçlü şifreleme, anahtarlama işlemı, güç tüketimi, enerji israfı, gecikme, uygulamaya özel, optimizasyon, haritalam
Doctor of Philosophy in Electrical and Electronic Engineering. Thesis (Ph.D.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Electrical and Electronic Engineering, 2016. Supervisor: Prof. Dr. Şener Uysal.
Keywords: Electrical and Electronic Engineering; Networks on a chip; Computer architecture; Computers; Systems Architecture; Computer Engineering; low power encoding; switching activity; power consumption; energy dissipation; latency; application specific; optimization; mapping